Daniel Tiger's neighborhood. School time fun! [videorecording (DVD)] - Santomero, Angela C. (PBS Kids, 2019)
It's field day at Daniel Tiger's school! Daniel and his friends play new games, and along the way they learn a lesson about the importance of trying your best. Daniel also takes a nature walk with his class and experiences the environment around him, plays 'school' with Baby Margaret, and takes a field trip to the library with his classmates.